Analysis of students error in global meta-level algebraic thinking on problem proving on CORE learning assisted by scaffolding - Ihtiani, Ana; Agoestanto, Arief (Unnes Journal of Mathematics Education, 2021)
The aims of this study are to identifies the quality of mathematics learning used CORE model assisted by scaffolding, examine whether students' ability in global meta-level algebraic thingking pass the minimun completeness criteria, describes the type and the causes of students error in global meta-level algebraic thingking, and type of scaffolding for lower group students. This is a mixed-method research. The population of this research are students of class XI-IPA at SMAN 1 Bojong. The sample of this research are students of class XI-IPA 3 as many as 32 students. The research subjects were taken 9 students, each of 3 students from the uuper, middle, and lower groups. Data collection methods used documentation, interviewies, and test. Teh validity of the data is done by triangulating the result of test and interviews. Data is analyzed by doing data reduction, data presentation, and verificatiton. The results of this research showed that (1) the quality of mathematics learning used CORE model assisted by scaffolding in very good criteria; (2 students' ability in global meta-level algebraic thingking on CORE learning assisted by scaffolding pass the minimun completeness criteria; (3) upper group students tend to make some error in the process skill and encoding steps, middle group students tend to make some error in the process skill steps, while lower group students tend to make some error in the transformation and process skill steps; (4) the cause of the error are lack of students’ accuracy in writing problem information modeling, inaccurate in calculation process, not able to complete the proving process, and inaccurate in writing down the variables in conclusion sentences; (5) scaffolding reviewing is given for transformation and encoding errors, scaffolding explaining, reviewing, and restructuring are given for process skill errors.